2022
DOI: 10.3389/fgene.2022.774196
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Estimates of Runs of Homozygosity, Heterozygosity, and Genetic Load in Two Chinese Indigenous Goat Breeds

Abstract: Runs of homozygosity (ROH) and heterozygosity (ROHet) are windows into population demographic history and adaptive evolution. Numerous studies have shown that deleterious mutations are enriched in the ROH of humans, pigs, cattle, and chickens. However, the relationship of deleterious variants to ROH and the pattern of ROHet in goats have been largely understudied. Here, 240 Guangfeng and Ganxi goats from Jiangxi Province, China, were genotyped using the Illumina GoatSNP50 BeadChip and genome-wide ROH, ROHet, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 93 publications
3
15
0
Order By: Relevance
“…It should also be noted that China, Italy, the United States stand out as key collaborating countries in the development and dissemination of genomic technologies, genetic studies, and bioinformatics related to polymorphisms, ROH, and inbreeding [4,[31][32][33][34]. Brazil in South America and Iran in Asia are recognized as emerging countries in this eld [35,36] (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that China, Italy, the United States stand out as key collaborating countries in the development and dissemination of genomic technologies, genetic studies, and bioinformatics related to polymorphisms, ROH, and inbreeding [4,[31][32][33][34]. Brazil in South America and Iran in Asia are recognized as emerging countries in this eld [35,36] (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…F ROH is affected by the ratio of long homozygous segments to whole-genome length and is less impacted by the quality of experimental materials and DNA samples [ 51 ]. This increases the accuracy of inbreeding coefficient calculation based on ROH in humans [ 7 ], cattle [ 9 ], pigs [ 10 ], sheep and goats [ 11 , 52 ], etc. In this study, the inbreeding coefficients among the 13 populations indicated that F ROH generally presented a lower value than the other indices.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, calculated runs of homozygosity (ROHs; long continuous homozygous stretches composed of two identical haplotypes in each individual) are more useful for elucidating inbreeding and detecting selection signatures in different populations [ 7 , 8 ]. This approach has been reported in cattle [ 9 ], pigs [ 10 ], goats [ 11 ], and chickens [ 12 ]. The inbreeding coefficient based on ROH (F ROH ) is more accurate and more closely represents real inbreeding at the population and individual levels, and a long ROH is more likely to be a result of recent inbreeding than a shorter ROH [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…DEGs were divided into up-DEGs and down-DEGs, and the correlation between DEGs and cuproptosis-related genes was analyzed using the website. 4 DE-CUGs were obtained for subsequent analysis.…”
Section: Identification Of Degs and De-cugsmentioning
confidence: 99%
“…Ganxi goats are an excellent local breed mainly raised in the western part of Jiangxi province, with the characteristics of small body size, strong adaptability, and a high reproductive rate. The existing studies mainly focus on transport stress ( 1 ), antioxidant capacity ( 2 ), intestinal immunity ( 3 ) and genome ( 4 ), but there is no study on wound healing in Ganxi goats. Therefore, in this study, transcriptomics was used for the first time to analyze the skin on 0d and 5d of wounds in Ganxi goats, and the physiological function of skin wound healing was discussed from the perspective of mRNA.…”
Section: Introductionmentioning
confidence: 99%